2019
DOI: 10.1002/hrm.21999
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic motivation as a determinant of knowledge exchange in sales teams: A social network approach

Abstract: This paper investigates extrinsic motivation as a determinant of knowledge exchange among employees in sales teams. Applying a social network approach, we study different forms of knowledge‐exchange behaviors from the perspective of a focal employee and from the perspective of the dyad. From the focal employees' perspective, we disentangle knowledge seeking from knowledge providing, and argue that these two behaviors are affected differently by employees' extrinsic motivation. From the dyad perspective, we tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 126 publications
0
13
0
Order By: Relevance
“…, 2019). High performance enables employees to be rewarded through incentives or promotion (David et al. , 2019).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…, 2019). High performance enables employees to be rewarded through incentives or promotion (David et al. , 2019).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Thus, the discrepancy of being abused between members strengthens emotional exhaustion under the same level of perceived abusive supervision, which further creates a spiral of resource loss. In total, two employees' relative levels determine their willingness to engage in reciprocal knowledge exchange (David et al, 2020). What is more, Mitchell et al (2015) suggested that when observers believe a coworker deserves the supervisor's abuse, they offer less support or show less sympathy to the coworker, which cannot make up for the lost emotional resource.…”
Section: Abusive Supervision and Knowledge Hidingmentioning
confidence: 99%
“…Personal reputation, group identification, and sharing willingness have different effects on the motivations, and team motivation has a specific effect as a regulator on relationships [32]. Furthermore, flexibility is necessary in order to connect people, as is ongoing communication [33], and extrinsic motivation is a crucial factor for knowledge sharing within a network [34].…”
Section: Collaborative Networkmentioning
confidence: 99%